The pelagic copepods of Lambert's Bay : an ecological study of a west coast fishing ground - Hopson, Susan Kate Dickerson (Department of Biological Sciences, 2016)
Monthly zooplankton samples were collected as part of the Cape Egg and Larva Survey from August 1977 - 1978. A line of stations from the coast to approximately 90 Kilometres offshore at Lambert's Bay was selected for intensive study because of its location in the middle of the recruitment area of South African anchovy and pilchard. Examination of physical features showed perennial moderate upwelling, with slight seasonal variation in frequency and intensity. Chlorophyll "a" levels were generally high. Zooplankton standing stock was surprisingly low considering the abundant phytoplankton, and this was attributed to intense predation resulting in high production/biomass ratios. Among the zooplankton, copepods were singled out for special attention because of their importance as food for larval fish. Only six species comprised 83% of the copepod community. These species displayed different spatial and temporal distribution, which appeared to be partly the result of size-determined life histories with indications of time/space niche partitioning. In comparison to the more intense seasonal upwelling area off the Cape Peninsula, there was a trend toward fewer species, larger animals, and more carnivores. This trend was related to changes in the physical and biotic environment.